Uncovering high rates of unsafe injection equipment reuse in rural Cameroon: validation of a survey instrument that probes for specific misconceptions - Reid Savanna R; Capo Mireille V; Alomba Fozao A; Ngem Bedes Y; Okwen Mbah P; Ewang Ebong C (BMC, 2011)
Abstract Background Unsafe reuse of injection equipment in hospitals is an on-going threat to patient safety in many parts of Africa. The extent of this problem is difficult to measure. Standard WHO injection safety assessment protocols used in the 2003 national injection safety assessment in Cameroon are problematic because health workers often behave differently under the observation of visitors. The main objective of this study is to assess the extent of unsafe injection equipment reuse and potential for blood-borne virus transmission in Cameroon. This can be done by probing for misconceptions about injection safety that explain reuse without sterilization. These misconceptions concern useless precautions against cross-contamination, i.e. "indirect reuse" of injection equipment. To investigate whether a shortage of supply explains unsafe reuse, we compared our survey data against records of purchases. Methods All health workers at public hospitals in two health districts in the Northwest Province of Cameroon were interviewed about their own injection practices. Injection equipment supply purchase records documented for January to December 2009 were compared with self-reported rates of syringe reuse. The number of HIV, HBV and HCV infections that result from unsafe medical injections in these health districts is estimated from the frequency of unsafe reuse, the number of injections performed, the probability that reused injection equipment had just been used on an infected patient, the size of the susceptible population, and the transmission efficiency of each virus in an injection. Results Injection equipment reuse occurs commonly in the Northwest Province of Cameroon, practiced by 44% of health workers at public hospitals. Self-reported rates of syringe reuse only partly explained by records on injection equipment supplied to these hospitals, showing a shortage of syringes where syringes are reused. Injection safety interventions could prevent an estimated 14-336 HIV infections, 248-661 HBV infections and 7-114 HCV infections each year in these health districts. Conclusions Injection safety assessments that probe for indirect reuse may be more effective than observational assessments. The autodisable syringe may be an appropriate solution to injection safety problems in some hospitals in Cameroon. Advocacy for injection safety interventions should be a public health priority.